2018
DOI: 10.12688/f1000research.15159.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and emerging therapies in the non-surgical management of ulcerative colitis

Abstract: The so-called “biologicals” (monoclonal antibodies to various inflammatory targets like tumor necrosis factor or integrins) have revolutionized the treatment of inflammatory bowel diseases. In ulcerative colitis, they have an established role in inducing remission in steroid-refractory disease and, thereafter, maintaining remission with or without azathioprine. Nevertheless, their limitations are also obvious: lack of primary response or loss of response during maintenance as well as various, in part severe, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 76 publications
0
43
0
1
Order By: Relevance
“…European guidelines recommend sustained steroid-free remission as the treatment goal. [7][8][9] Despite these options, some patients with UC require a colectomy. 10 The highest colectomy rates are seen during the first few years after diagnosis.…”
Section: Key Messagesmentioning
confidence: 99%
“…European guidelines recommend sustained steroid-free remission as the treatment goal. [7][8][9] Despite these options, some patients with UC require a colectomy. 10 The highest colectomy rates are seen during the first few years after diagnosis.…”
Section: Key Messagesmentioning
confidence: 99%
“…Ulcerative colitis (UC) which characterize by recurring inflammation of the bowel not only brings financial strain, but also affects patients quality of life (QoL). [ 1 , 5 , 24 ] The theory of acupoints embedding is from Chinese medicine, which can balance the bodys yin and yang by continuously stimulating acupuncture points. It is getting more and more attention as a form of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 2 ] UC occurs on the surface of the intestinal mucosa, starting the rectum and then spreading to the entire colon. [ 3 , 4 ] In recent years, it is becoming a global disease, publications showed that UC is not only occurring in Western countries, [ 5 7 ] but is also increasing in developing regions such as Asia and Africa, 1 study showed that there was a six-fold increase of incidence from 1986–1988 to 2004–2006 in Hong Kong. [ 8 ] About the pathogenesis of UC, there is still no specific clinical conclusion, but most people think it is related to environment, genetics and immune.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs blocking pleiotropic proinflammatory pathways, such as steroids, immunomodulatory drugs, anti‐TNF agents, the Th1/Th17 axis via IL‐12/23 blockage and leucocyte trafficking via anti‐integrins and signalling molecules, are the mainstay of medical management of IBD . These agents are fairly effective, with steroid‐free clinical remission rates ranging from 57% for combination therapy with infliximab (anti‐TNF) and azathioprine (thiopurine) to 18% for tofactinib [targets Janus kinase/signal transducers and activators of transcription (JAK/STAT) signalling pathway] . With increasing evidence of a dysregulated intestinal microbiome being a probable immunological trigger for inflammation in IBD, exploring therapeutic manipulation of the gut microbiome is an attractive strategy to identify new treatment options, and help understand the underlying cause of IBD.…”
Section: Exploring Gut Microbiota Manipulation For Treatment Of Ibdmentioning
confidence: 99%